POLLUTION OF MINING INDUSTRY SULFUR PURIFICATION PLANT AT AL MISHRAQ (Journal of Engineering, 2011)
The Al Mishraq site has been the subject of many scientific studies for the period before andafter the fire in 2003. Five visits to the site were conducted twice in 2003 for general fact-finding, twicein 2004, and once in 2005 for detailed sampling and monitoring. Desk-based research and laboratory analysis of soil and water samples results indicate that surface water and groundwater pollution from Al Mishraq site was significant at the time of its operation. The primary pollution source was the superheated water injection process, while the principal receptor is the River Tigris. Now that the plant is idle, this source is absent. Following the June 2003 sulphur fire, initial investigations indicate that short damage tovegetation was severe close to the plant but there is no evidence of widespread or significant long-termdamage. Rainwater and drainage ponds and gullies close to the sulphur processing and acid containhazardous levels of acid. Runoff from these areas may be affecting local water quality. There is regional moderate groundwater contamination by sulphate and hydrogen sulphide, but much of this may be naturally sourced. The site in its current state represents a low risk to human health and the environmentprincipally due to the acidic surface water ponds, but in the absence of corrective action, the hazardlevels may be elevated after some decades.